Diseases of the Pomegranate Tree - Ubaydullaeva Shakhista Hdoyatillo Qizi (Zien Journals, 2023)
The fecundity of the pomegranate limits the high effectiveness of insecticides, which give many generations and develop in a hidden form, penetrating into the fetus. This article discusses the pomegranate tree, its characteristics and the classics of the pomegranate tree.
Keywords: pomegranate fruit; pomegranate tree; properties; insects and spiders